Research of self-adaptive PID drilling fluid level control algorithm based on differential flow - Li, Lei; Deng, Hu; Dong, Zhigang (Journal of physics. Conference series, 2020)
Aimed at the puzzle of traditional PID control algorithm not satisfy level control requirement when drilling fluid performance changing, the article proposed adaptive PID level control algorithm based on differential flow. Through monitoring differential flow between slurry pump outlet and buffer pry inlet, the algorithm got optimized PID control parameters and evaluated drilling fluid properties, which could be used for liquid level control under different fluid medium characteristics. In the laboratory test of drilling fluid tank, the proposed algorithm could always keep the level deviation within 5% through self-adaptive modify PID control parameters under different drilling fluid characteristics. The results shows that the algorithm has wide adaptability and high reliability, and can be applied to the liquid level control situation where the characteristics of the fluid medium change.